2020
DOI: 10.1371/journal.pone.0232239
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric social networks, lifestyle behaviors, and body size in the Asian Community Health Initiative (CHI) cohort

Abstract: Background Social networks have been shown to influence lifestyle behaviors in non-Latinx white (NLW) populations. We examined their influence in Asian American, Native Hawaiian and Pacific Islander (AANHPI) women. Methods We included 477 AANHPI women from the Asian Community Health Initiative Study who provided egocentric (degree, density, composition) and epidemiologic (size, types of ties) social network data and data on alcohol intake, physical activity, smoking, diet, and body size. We used logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…39 Similarly, another study found greater number of friends in one's network was related to a greater likelihood of meeting PA recommendations. 40 However, one study reported the presence of family members in networks to be positively associated with PA. 33 Tie strength and reciprocity were also important for PA behavior. Specifically, parent-child dyads were 8 times more likely to engage in PA together if they shared a close relationship and were over 5 times more likely to do so if there was also reciprocal encouragement between the parent and child to do regular PA. 41 Additionally, the association between encouragement for PA and co-participation in PA was found to be significant only when this relationship was reciprocal, not when the encouragement relationship was unilateral.…”
Section: Resultsmentioning
confidence: 99%
“…39 Similarly, another study found greater number of friends in one's network was related to a greater likelihood of meeting PA recommendations. 40 However, one study reported the presence of family members in networks to be positively associated with PA. 33 Tie strength and reciprocity were also important for PA behavior. Specifically, parent-child dyads were 8 times more likely to engage in PA together if they shared a close relationship and were over 5 times more likely to do so if there was also reciprocal encouragement between the parent and child to do regular PA. 41 Additionally, the association between encouragement for PA and co-participation in PA was found to be significant only when this relationship was reciprocal, not when the encouragement relationship was unilateral.…”
Section: Resultsmentioning
confidence: 99%